2021
DOI: 10.1111/twec.13109
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the World Trade Organization on new members

Abstract: In recent years, there has been intense debate on the effects of the World Trade Organization (WTO) and its predecessor, the General Agreement on Tariffs and Trade (GATT) on global trade, triggered by Rose’s article (2004) suggesting that the WTO/GATT did not promote world trade at all. In addition, Subramanian and Wei (2007) pointed out a series of asymmetries in trade liberalization led by international organizations. In this paper, we estimate the WTO impact on new members considering both total and disaggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Natural determinants such as GDP, geographical distance, and population have a significant impact on green trade, which is consistent with theoretical expectations (Cardebat and Alexandru, 2013;Borchert and Yotov, 2017). We also found that the population of China and other RCEP countries have different impacts on trade value, which is consistent with the study of Reis et al (2021). This is because the diverse demands of population growth promote international trade, while providing labor and technology for domestic production, which offsets international trade to some extent.…”
Section: Estimation Of Green Trade Potentialsupporting
confidence: 88%
“…Natural determinants such as GDP, geographical distance, and population have a significant impact on green trade, which is consistent with theoretical expectations (Cardebat and Alexandru, 2013;Borchert and Yotov, 2017). We also found that the population of China and other RCEP countries have different impacts on trade value, which is consistent with the study of Reis et al (2021). This is because the diverse demands of population growth promote international trade, while providing labor and technology for domestic production, which offsets international trade to some extent.…”
Section: Estimation Of Green Trade Potentialsupporting
confidence: 88%
“…The literature has also established that the WTO membership has led to a significant expansion of trade, including both exports and imports flows (for example, Allee and Scalera, 2012;Chang and Lee, 2011;dos Reis et al, 2021;Dutt, 2020;Dutt et al 2013;Eicher and Henn, 2011;Larch et al, 2019;Subramanian and Wei, 2007;Tomz et al, 2007). In light of these findings, and given the discussion laid down in sub-section 3.3., we surmise that even though the membership in the WTO has restricted developing countries' trade policy space, countries that have used ingeniously the available trade policy space in WTO law to advance their trade development agenda, are likely the ones that have enjoyed a higher degree of integration into the world trade market.…”
Section: Hypotheses To Be Testedmentioning
confidence: 98%
“…Por lo tanto, está claro que la configuración del sistema multilateral de comercio, como se lo conoce hoy, ha sido resultado de un proceso arduo el cual comenzó en 1947 con la aprobación exitosa de la Carta de La Habana, que también incluía la creación de una figura conocida, en ese entonces, como la Organización Internacional de Comercio (OIC). Así este proyecto se intentaba concebir como una institución internacional para la regulación del comercio entre las partes contratantes del GATT; sin embargo, esta propuesta finalmente fracasó debido a la falta de aprobación del Congreso de los Estados Unidos como también a la falta de voluntad política entre las partes, una situación que sin dudas representó un gran revés para los inicios del sistema multilateral de comercio dada la ausencia de Estados Unidos como líder mundial a nivel económico (REIS, 2009).…”
Section: Introductionunclassified